Caste differences in behaviour and personality: Evidence from India - Utteeyo Dasgupta; Subha Mani; Smriti Sharma; Saurabh Singhal (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
The persistent gap in economic outcomes between the upper and lower caste groups in India is typically explained through differences in endowments and the presence of discrimination. While there is sizable literature that examines caste gaps in physical and intellectual human capital, this paper contributes to a small literature that evaluates caste differentials in behavioural preferences and personality traits that are possibly associated with the persistent economic gap between these castes. Using data from experiments and surveys conducted among a large sample of Indian undergraduate students, we find significant caste differences in behaviour and personality such that Scheduled Castes, Scheduled Tribes, and Other Backward Classes are less likely to be endowed with the behavioural preferences and personality traits that tend to affect educational attainment, labour market performance, and overall wellbeing positively. Our results have implications for revising the focus of current caste-based policy formulations.
Keywords: I23; C9; C18; J24; O15; 330; behaviour; personality; caste; artefactual field experiments; India